2021
DOI: 10.1016/j.jare.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Iminostilbene, a novel small-molecule modulator of PKM2, suppresses macrophage inflammation in myocardial ischemia–reperfusion injury

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Inflammation was a key factor in the MI/R injury [ 21 ], and oxidative stress was also closely related to inflammation. IL-6 was significantly increased during hypoxia in cardiomyocytes [ 22 ], while iNOS is a classical inflammatory factor.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation was a key factor in the MI/R injury [ 21 ], and oxidative stress was also closely related to inflammation. IL-6 was significantly increased during hypoxia in cardiomyocytes [ 22 ], while iNOS is a classical inflammatory factor.…”
Section: Resultsmentioning
confidence: 99%
“…24 Recombinant PKM2 confers neuroprotective effects against ischemic damages, 25 and iminostilbene binds to PKM2 to reduce myocardial infarction, and improves cardiac function in rats with myocardial ischemia/reperfusion injury model. 26 Therefore, PKM2 might be involved in JMJD5/HIF-1α-mediated protective effect against myocardial infarction. However, further investigation will be required to elucidate this.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response is a very complex biological process, which has an important role in many diseases ( Costa et al., 2021 ; Li et al., 2021 ; Lu et al., 2021 ; Wang J. et al., 2021 ). Previous studies showed that inflammatory response played a critical role in the onset of depression, and the disturbance of inflammation levels could increase the incidence of depression ( Leonard, 2018 ; Colasanto et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%